ICES TABLE-I : an ICES file storage subsystem; engineering user' manual - 463220 Logcher, Robert D.; Power, Conor M.; Kwok, Hae L. (Cambridge, Mass. : Civil Engineering Systems Laboratory, MIT, 1967)
09